Integration Strategies and Competitive Advantage in Manufacturing Sector: Evidence from Ogun State, Nigeria - Izediuno, Okafor Linus; Eugenia, Ifekwem Nkiruka; Akande, Bello Bashiru; Adunola, Ajayi Mobolanle; Bamigbaiye-Elatuyi, Omotola; Oladunke, Adebiyi Omolola; Aliyu, Modibbo Usman; Theodore, Nnoli Ikenna (International Review of Management and Marketing, 2024)
The study examined the joint impact of vertical and horizontal strategies on competitive advantage. Data were collected from primary sources using a questionnaire Survey, administered to employees of ten manufacturing firms in Ogun state. A total of three hundred and eighty-four (384) copies of the questionnaire were distributed to the selected respondents as arrived at using the Taro Ya-mane formula. The hypotheses of the study were tested using the Pearson correlation coefficient and multiple regression analysis in other to determine whether to accept or reject the null hypotheses (H0). The results of the Pearson correlation coefficient rejected the null hypotheses (Null hypotheses 1 and 2) and accepted the alternative hypotheses 1 and 2. The final hypothesis was tested using multiple regression analysis. The result showed that both vertical integration strategies and horizontal integration strategy with coefficients of 0.556 and 0.843 had a positive and significant impact on competitive advantage. From the findings of the study, the study recommended that collaboration between companies in the same industry can lead to improved vertical integration and increased competitive advantage. The government should therefore encourage such collaboration through the creation of industry associations or other forums where companies can share knowledge and best practices.